2018
DOI: 10.1097/gme.0000000000001053
|View full text |Cite|
|
Sign up to set email alerts
|

Fractional microablative CO2 laser in breast cancer survivors affected by iatrogenic vulvovaginal atrophy after failure of nonestrogenic local treatments: a retrospective study

Abstract: This study shows that CO2 laser treatment is effective and safe in BC patients with iatrogenic menopause. However, the optimal number of cycles to administer and the need for retreatment remain to be defined. Prospective trials are needed to compare CO2 laser therapy with therapeutic alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 31 publications
4
66
0
Order By: Relevance
“…This limited study drew similar conclusions to those reached for other women and was hindered by similar study design flaws. 70,71,76 Recent developments for the use of LASER in women with GSM/VVA include an international multicenter observational study aiming to evaluate 1500 women treated with vaginal Er:YAG LASER. 77 There is also an ongoing randomized study comparing the effects of CO 2 LASER to vaginal estrogen treatment.…”
Section: Impact On the Vaginal Microbiomementioning
confidence: 99%
“…This limited study drew similar conclusions to those reached for other women and was hindered by similar study design flaws. 70,71,76 Recent developments for the use of LASER in women with GSM/VVA include an international multicenter observational study aiming to evaluate 1500 women treated with vaginal Er:YAG LASER. 77 There is also an ongoing randomized study comparing the effects of CO 2 LASER to vaginal estrogen treatment.…”
Section: Impact On the Vaginal Microbiomementioning
confidence: 99%
“…Ten studies included breast cancer survivors. [43][44][45][46][47][48][49][50][51][52] Below, we discuss the studies in terms of the therapeutic modality used. We present the results in terms of histological changes, physician assessment, subjective patient reports, adverse events, author recommendations and long-term outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…47 Seven studies included women with a history of breast cancer. 44,45,[47][48][49][50]52 Histological changes Samuels & Garcia 59 performed biopsies in 'several' postmenopausal women immediately before the first treatment and then at 3-and 6-month follow-up visits after the total of three treatments. Histological review at 3-month followup showed increased collagen and elastin, a thicker epithelium, an increased number of cell layers and a better degree of surface maturation in all patients.…”
Section: Co 2 Lasersmentioning
confidence: 99%
See 2 more Smart Citations